Intensive knowledge engineering for the management of internal supply chains - Zhao, Zhenying. (2008)
The management of an internal supply chain aims at improving the performance of the material flow via the information flow within an enterprise. This study argues that intensive knowledge and computer simulation play a profound role in both the modelling and management of advanced internal supply chains. Therefore, a novel intensive knowledge processing and utilization technique, named as intensive knowledge engineering, is initiated, and an integrated infrastructure for the management of internal supply chains based on computer simulation is proposed in this research.